Routledge Handbook of Mental Health Law - Kelly, Brendan D.; Donnelly, Mary (Taylor & Francis, 2024)
Children and mental health law; Decision-making capacity; Justice and mental health law; Mental health law; UN Convention on Rights of the person with disabilities; World Health Organization's QualityRights Initiative; coercion; forensic psychiatry and criminal law; gender and mental health law; human rights; involuntary psychiatric treatment; mental health and criminal law; older adults and mental health law